The Impact of Job Fit and Psychological Climate in the Air Navigation Service Industry on Employee Performance Through Employee Engagement and Job Satisfaction - Zakiah Agus; Dimas Angga Negoro (Jurnal Ekonomi Manajemen Sistem Informasi, 2026)
The purpose of this study was to analyze the impact of job fit and psychological climate on employee performance in the air navigation service industry, considering the mediating roles of employee engagement and job satisfaction. In a demanding and high-risk work environment such as air navigation, job fit and psychological climate are thought to have a significant influence on employees’ engagement and job satisfaction, which in turn affects employee performance. The study employs a quantitative approach using a survey method, involving 228 employees of AirNav Indonesia working as Air Traffic Controllers (ATC) at the Jakarta Air Traffic Service Center (JATSC) Branch Office. Participants were required to have a minimum of four years of work experience and a surveillance rating. The analysis utilized factor analysis and structural equation modeling (SEM-PLS). The results of the study indicate that for AirNav Indonesia employees serving as ATCs at the JATSC Branch Office, higher job fit correlates with increased levels of and job satisfaction. Similarly, fostering a positive psychological climate significantly influences employee engagement and job satisfaction. When employee engagement and job satisfaction are well-established, they contribute to improved employee performance. The implications of this study highlight the importance of organizations creating job fit and supporting a positive psychological climate to enhance employee engagement, job satisfaction, and overall performance.